Preventing, curing, mitigating: Anti-segregation policies in urban Finland - Ruonavaara, Hannu; Rasinkangas, Jarkko; Rosengren, Katriina (ELSEVIER SCI LTD, 2025)
The purpose of this research is (1) to develop a conceptual framework for analyzing policies against residential segregation and (2) to apply it in inquiring about anti-segregation policy (ASP) inthree core cities in Finland: Helsinki, Tampere, and Turku. First, we develop a functional typology of preventive, curing, and mitigating ASP. Second, we cross-tabulate it with an operational typology of three kinds of ASPs, population dispersion, social mixing, and area-based projects, to create a combined typology of ASPs. With the help of combined typology, we analyze our primary empirical material and policy documents in the three cities. We ask two questions: 1) How do the three cities respond to a growing concern about residential segregation and its negative consequences? 2) How do their responses relate to our combined typology of ASPs? We find no notable differences in the palette of ASPs used in the three cities. However, Helsinki differs to some extent from the other two with its longer history of ASP and wider coverage of different policy instruments. All three cities use preventive and, to some extent, curing social mixing policies: trying to balance population structure in planning new neighborhoods and infill building in old neighborhoods. All cities use mitigating area-based policies, such as social policy interventions in vulnerable neighborhoods. We can tentatively say that this is the Finnish approach to segregation prevention. It does not include curing dispersal measures such as demolishing housing estates to change the population structure or limiting the share of particular population groups in residential areas.